Trying Out New Paths in Aesthetics - Ryynänen, Max; Somhegyi, Zoltán (Historical and Philosophical Aesthetics, 2026)
This book focuses on one of the all-time primary interests of all researchers-finding new perspectives and research topics-and expands it. What new routes could aesthetics, philosophy of art and the aesthetic take today and in the future? Thirteen authors open new doors for the discipline to new companion disciplines, new discussions, and new concepts. Heritage studies, Greek aesthetic concepts, found literature, power, safety and mythology, monuments, artificial intelligence, sensibility, hybrid spaces, textiles, aesthetics of AI, aesthetics of literature, aesthetic values, homo ludens and martial arts studies are approached in new ways in this volume, where the spearhead lies in thinking about the next step of the ancient discipline of aesthetics and what potential it could have for the world of research in the future.